Differences in bone mineral density and associated factors in dancers and other female athletes - Critchley, M. L.; Toomey, C.; Gabel, L.; Kenny, S. J.; Emery, C. A. (Applied Physiology, Nutrition, and Metabolism, 2024)
Dancers are susceptible to relative energy deficiency in sport (RED-S), specifically low bone mineral density (BMD). Little is known about how dancers` BMD compares to other athletic populations. The objective of this study was to examine the association between participant characteristics and total body areal BMD (aBMD) among female pre-professional dancers compared to other female athletes. Two hundred sixty-nine females (132 pre-professional dancers (17.6 (3.2) years) and 137 sport participants (22.8 (2.6) years) were included in this study. aBMD (g/cm2) was estimated using dual X-ray absorptiometry. Multivariable linear regression was used to examine the association between height-adjusted z-scores of total body aBMD (aBMD-Z) and age (years), body mass index (BMI) (z-score), supplement intake, history of stress fracture, irregular menses, MRI/bone scan, 1-year injury history, oral contraceptives, and activity (dance/sport). Total body aBMD and aBMD-Z were lower in dancers than athletes (dancers: aBMD = 1.03 g/cm2 (95% CI: 1.01, 1.05); aBMD-Z = -0.28 (-0.43, -0.12) (p < 0.001); athletes: aBMD = 1.14 g/cm2 (95% CI: 1.12, 1.16); aBMD-Z = 0.41 (0.25, 0.57) (p < 0.001)). aBMD-Z increased with age (ß = 0.054, 95% CI: 0.017, 0.092; p = 0.004) and BMI (ß = 0.221, 95% CI: 0.006, 0.415; p = 0.043). Activity type modified the relationship between BMI and aBMD-Z (ß = 0.323, 95% CI: 0.025, 0.621; p < 0.033) with a stronger positive association in dancers, compared to other female athletes. Dancers had lower total body aBMD and aBMD-Z than other female athletes. aBMD-Z increases with age in female pre-professional dancers and other female athletes. A stronger association exists between aBMD-Z and BMI in dancers than athletes. Future studies should consider changes in aBMD-Z during adolescence and associations with increased risk of bone injury.